1996
DOI: 10.1038/nm0896-893
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and protective efficacy of a tuberculosis DNA vaccine

Abstract: Tuberculosis is the most widespread and lethal infectious disease affecting humans. Immunization of mice with plasmid DNA constructs encoding one of the secreted components of Mycobacterium tuberculosis, antigen 85 (Ag85), induced substantial humoral and cell-mediated immune responses and conferred significant protection against challenge with live M. tuberculosis and M. bovis bacille Calmette-Guérin (BCG). These results indicate that immunization with DNA encoding a mycobacterial antigen provides an efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
380
3
6

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 589 publications
(410 citation statements)
references
References 27 publications
21
380
3
6
Order By: Relevance
“…Moreover, mouse immunization experiments have shown that vaccination with DNA encoding Ag85A could generate strong CD4 + T-cell-mediated Th1 and CD8 + T-cell-mediated CTL responses and be responsible for improved protection against challenge by virulent M. tuberculosis in animal models. [15][16][17] In the present study, we demonstrate for the first time that Ag85A DNA vaccine could also be effective at reducing the reactivation of established M. tuberculosis (Table 1 and Figure 4). Rates of reactivation in both lungs and spleens were found to be inversely correlated with the Ag85A-specific IFN-g production level, but not with the CFspecific IFN-g level (Figures 3a and b), indicating that Ag85A-specific Th1 immunity may be more important than Th1 immune response specific for CF in terms of protection against M. tuberculosis reactivation.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, mouse immunization experiments have shown that vaccination with DNA encoding Ag85A could generate strong CD4 + T-cell-mediated Th1 and CD8 + T-cell-mediated CTL responses and be responsible for improved protection against challenge by virulent M. tuberculosis in animal models. [15][16][17] In the present study, we demonstrate for the first time that Ag85A DNA vaccine could also be effective at reducing the reactivation of established M. tuberculosis (Table 1 and Figure 4). Rates of reactivation in both lungs and spleens were found to be inversely correlated with the Ag85A-specific IFN-g production level, but not with the CFspecific IFN-g level (Figures 3a and b), indicating that Ag85A-specific Th1 immunity may be more important than Th1 immune response specific for CF in terms of protection against M. tuberculosis reactivation.…”
Section: Discussionmentioning
confidence: 54%
“…Prophylactic DNA vaccines expressing M. tuberculosis antigens or cytokines are of particular interest, because of their efficiency and long-lasting effect in animal TB models. For example, prophylactic DNA vaccines expressing various M. tuberculosis antigens, including Ag85A, [15][16][17] Ag85B, 17,18 65 kDa heat shock protein, 19,20 and PstS-3 21 , were found to be effective at limiting the growth of M. tuberculosis in mice. In contrast, there has been little evidence that DNA vaccines are useful as therapeutic vaccines against TB.…”
Section: Introductionmentioning
confidence: 99%
“…In prophylactic settings, there are several reports that DNA vaccines expressing M. tuberculosis antigens are effective for limiting the bacterial growth in mice. [10][11][12][13] However, it is still controversial whether DNA vaccines work against TB reactivation in postexposure models. [14][15][16] For example, the vaccination of plasmid DNA expressing hsp65 after completion of chemotherapy was shown to be effective in preventing the reactivation of intravenously infected M. tuberculosis.…”
mentioning
confidence: 99%
“…Hence, a Th1 response is probably required for 10,18,19 In contrast, a Th2 response is abundant during infection with M. tuberculosis, and thus a shift in the balance toward a Th1 response may be beneficial. 20,21 DNA vaccination can achieve such a shift particularly because of its own 'adjuvant' effect.…”
Section: Discussionmentioning
confidence: 99%